MicroRNA-194-5p Attenuates Doxorubicin-Induced Cardiomyocyte Apoptosis and Endoplasmic Reticulum Stress by Targeting P21-Activated Kinase 2 - Fa, Hongge; Xiao, Dandan; Chang, Wenguang; Ding, Lin; Yang, Lanting; Wang, Yu; Wang, Mengyu; Wang, Jianxun (Frontiers in Cardiovascular Medicine, 2022)
Objective Many studies have reported that microRNAs (miRs) are involved in the regulation of doxorubicin (DOX)-induced cardiotoxicity. MiR-194-5p has been reported significantly upregulated in patients with myocardial infarction; however, its role in myocardial diseases is still unclear. Various stimuluses can trigger the endoplasmic reticulum (ER) stress and it may activate the apoptosis signals eventually. This study aims to explore the regulatory role of miR-194-5p in DOX-induced ER stress and cardiomyocyte apoptosis. Methods H9c2 was treated with 2 μM DOX to induce apoptosis, which is to stimulate the DOX-induced cardiotoxicity model. The expression of miR-194-5p was detected by quantitative real-time PCR (qRT-PCR); the interaction between miR-194-5p and P21-activated kinase 2 (PAK2) was tested by dual luciferase reporter assay; terminal deoxynucleotidyl transferase dUTP nick-end labeling (TUNEL) assay and caspase-3/7 activity were used to assess apoptosis; trypan blue staining was applied to measure cell death; Western blotting was performed to detect protein expressions; and ER-related factors splicing X-box binding protein 1 (XBP1s) was detected by polyacrylamide gel electrophoresis and immunofluorescence to verify the activation of ER stress. Results MiR-194-5p was upregulated in cardiomyocytes and mouse heart tissue with DOX treatment, while the protein level of PAK2 was downregulated. PAK2 was predicted as the target of miR-194-5p; hence, dual luciferase reporter assay indicated that miR-194-5p directly interacted with PAK2 and inhibited its expression. TUNEL assay, caspase-3/7 activity test, and trypan blue stain results showed that either inhibition of miR-194-5p or overexpression of PAK2 reduced DOX-induced cardiomyocyte apoptosis. Silencing of miR-194-5p also improved DOX-induced cardiac dysfunction. In addition, DOX could induce ER stress in H9c2, which led to XBP1 and caspase-12 activation. The expression level of XBP1s with DOX treatment increased first then decreased. Overexpression of XBP1s suppressed DOX-induced caspase-3/7 activity elevation as well as the expression of cleaved caspase-12, which protected cardiomyocyte from apoptosis. Additionally, the activation of XBP1s was regulated by miR-194-5p and PAK2. Conclusion Our findings revealed that silencing miR-194-5p could alleviate DOX-induced cardiotoxicity via PAK2 and XBP1s in vitro and in vivo. Thus, the novel miR-194-5p/PAK2/XBP1s axis might be the potential prevention/treatment targets for cancer patients receiving DOX treatment.